1996
DOI: 10.1088/0029-5515/36/1/i02
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the resistive shell mode in tokamaks

Abstract: The stability of current-driven external-kink modes is investigated in a tokamak plasma surrounded by an external shell of finite electrical conductivity. According to conventional theory, the ideal mode can be stabilized by placing the shell sufficiently close to the plasma, but the non-rotating "resistive shell mode," which grows on the characteristic L/R time of the shell, always persists. It is demonstrated, using both analytic and numerical techniques, that a combination of strong edge plasma rotation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 29 publications
6
141
2
Order By: Relevance
“…It remains a key challenge for the advanced tokamak program to demonstrate resistive wall stabilization at beta values significantly beyond the no-wall value for long durations. Sustained plasma rotation and active non-axisymmetric feedback stabilization (Fitzpatrick 1996, Jensen 1997 are presently thought to be the means to meet this challenge.…”
Section: Ts Taylormentioning
confidence: 99%
“…It remains a key challenge for the advanced tokamak program to demonstrate resistive wall stabilization at beta values significantly beyond the no-wall value for long durations. Sustained plasma rotation and active non-axisymmetric feedback stabilization (Fitzpatrick 1996, Jensen 1997 are presently thought to be the means to meet this challenge.…”
Section: Ts Taylormentioning
confidence: 99%
“…In these experiments, there is a rapid toroidal rotation due to unbalanced neutral beam injection. Theoretically, it is shown that the combination of plasma rotation and some dissipation model can stabilize RWMs [4][5][6][7]. When the RWMs are destabilized, the RWM results in major collapse.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 There is another possible mechanism for the stabilization of RWMs, described by Fitzpatrick and Aydemir. 12 This relies on the existence of a cool and viscous edge region at the plasma edge, which plays a similar role ͑i.e., providing dissipation and drag͒ to that of the internal resonant surfaces. In Ref.…”
mentioning
confidence: 99%